Gender-Technology-Trust: Feminist Reflections on Mobile and Social Media Practices. Issue 107 (2nd January 2021) - Hardley, Jess; McGrane, Caitlin; Richardson, Ingrid
ABSTRACT: This special issue of Australian Feminist Studies aims to make an interdisciplinary contribution to ongoing feminist conversations around gender, technology and trust – with a particular focus on mobile and social media debates, dialogues and empirical examples. We strategically conceptualise the contingent relationality of gender and technology and trust as a hyphenated assemblage of 'gender-technology-trust', and foreground the complex, ambiguous, and nuanced theoretical and empirical development and analysis of what it means to 'trust' in the age of ubiquitous mobile and social media. The five articles and one interview included in this special issue emerge from the global and Australian context (ranging across rural and urban settings), and brings together feminist scholars to critically engage with gender-technology-trust relations that characterise quotidian life.